The effect of granulated sugar application on healing in the treatment of infected wounds and abscesses - Nuri Yavru; Yılmaz Koç; Mustafa Ancan; Yusuf Doğruer (Eurasian Journal of Veterinary Sciences)
With this study it was tried to use the rather simple, cheap and uncomplicated treatment method of crystallise sugar application as an help of treatment in the field of veterinary medicine. In this study materials were consisted of total 28 cases; these were; 1 dog, 1 rabbits, 2 horses and 4 cattle which had been brought to the surgery clinics. 1 horse, 2 catle had bursitis purulenta, 2 calves had arthritis purulenta, 1 cat, 1 sheep, 4 horses, 3 cattle had infected and necrotic wounds, 6 dogs had experimentally made symetric wounds. Granulated sugar was applied in crystallise form as 40% solution and 59% paste form. One of the experimentally made wounds was treated in clasical medhod, and the next one is by grunulated sugar application. Any antibiotic was used expect in arthritis purulenta cases. The resistance of the wound was measured comparatively with an electronic prebe (Eastern-Animdletek-lnc. USA) in order tohave an idea about the improvement rate of the healing results of granulation tissue of experimentally made wounds in 3 dogs. From the other 3 dogs 1 gram of muscle piece was taken before and third and sixth day after the treatment in order to detect the bacteria level on both of the wounds, that colony counts were made. Putrid flow from abscesses in different dimensions has stopped varying in time of 3 to 5 days by application of 40 % granulated sugar solution. This time was obtained as 4 days in arthritis and 2-3 days in bursitis cases. Complete healing was in between 10-17 days. In the infected wounds it was detected that production of granulation tissue by ceasing of flow occured in 3 to 5 days depending on the size of the wound, it has neeted 7 to 13 days for granulation tissue to reach to the skin level. It was reported that the regression of the size of the wound half of its original size on the fifth day and a higher resistance of sugar applied wound was detected in the measurements of the granulation tissue improvement. Reduction of bacteria number was detected in sugar applied wounds comparing with the other one in colony countings bacteriologically. Findings at the end of this study was showed that because of good results, cheapness, easily applicabliness and most abundancy of sugar it may be an alternative to other classical treatment methods.